Producing Ignorance Through Regulatory Structure: The Case of Per- and Polyfluoroalkyl Substances (PFAS). (August 2021) - Richter, Lauren; Cordner, Alissa; Brown, Phil
This article examines how ignorance can be produced by regulatory systems. Using the case of contamination from per- and polyfluoroalkyl substances (PFAS), we identify patterns of institutionalized ignorance in U.S. chemical regulation. Drawing on in-depth interviews and archival research, we develop a chemical regulatory pathway approach to study knowledge and ignorance production through the regulatory framework, the Toxic Substances Control Act (TSCA). Investigating TSCA's operation, we consider why PFAS were relatively recently recognized as a significant public health threat, despite evidence of their risks in the 1960s. The historical context of TSCA's enactment, including the mobilization of the chemical industry, contributed to the institutionalization of organizational practices promoting distinct types of ignorance based on stakeholder position: chemical manufacturers who have discretion over knowledge production and dissemination, regulators who operate under selective ignorance, and communities and consumers who experience nescience, or total surprise.